2009
DOI: 10.1111/j.1751-553x.2008.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin A2′ and its significance in β thalassaemia diagnosis

Abstract: We have studied, haemoglobin A(2)' (A(2) prime), a delta chain variant haemoglobin occurring in a small percentage of individuals of African ancestry. In heterozygotes, the percentage of haemoglobin A(2)' was found to be slightly lower then the percentage of haemoglobin A(2), suggesting that the variant delta chain is synthesized at a reduced rate. When quantifying haemoglobin A(2) for the diagnosis of beta thalassaemia heterozygosity, it is essential to add together the A(2) and A(2)' to give 'total haemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Retention time of a hemoglobin variant can change with different lots of reagents (including the ion-exchange column)[15]. The levels of HbA2 were found to be higher than those of HbA2' in all cases similar to other published reports [2,6,14,16]. All cases with suspected HbA2' of >2% fell under the category of β-thalassaemia minor if S-window peak was taken into account, which was also consistent with previously published studies [10,14].…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Retention time of a hemoglobin variant can change with different lots of reagents (including the ion-exchange column)[15]. The levels of HbA2 were found to be higher than those of HbA2' in all cases similar to other published reports [2,6,14,16]. All cases with suspected HbA2' of >2% fell under the category of β-thalassaemia minor if S-window peak was taken into account, which was also consistent with previously published studies [10,14].…”
Section: Resultssupporting
confidence: 82%
“…HPLC has been shown to be a reliable instrument for the detection of HbA2' in many parts of the world [6,13,14]. We found that the trends (retention time etc.)…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations